New pump delivery scheme for remotely pumped L-band erbium-doped fiber amplifier - Abu Bakar, Muhammad Hafiz (2012)
Several enhancements to the pump delivery scheme for remotely pumped L-band erbium-doped fiber amplifier (R-EDFA) were investigated in this research. The proposed pumping scheme utilized stimulated Raman scattering (SRS) generated during the pump light propagation and use it as a pump in order to improve the performance of the L-band amplifier. The pumping scheme took advantage of the SRS and utilizes it as a higher-order pump source to increase the amount of pump power available for amplification. Initially, the proposed pumping scheme was focused on the pump delivered to the R-EDFA itself. Two Raman laser wavelengths at 1455 and 1423 nm were tested as the primary pump. A total of 44.5 mW delivered pump power was derived from the 1455 nm laser and the 1555 nm SRS second-order pump. Amplification of the SRS saturated the R-EDFA and induced gain-clamping effect. The SRS also contributed to the generation of 1567 nm laser in the transmission line that dominated the Raman amplification and reduced the transmission gain and optical signal-to-noise ratio (OSNR) at the shorter L-band wavelengths. The utilization of SRS at 1512 nm eliminated the effect of gain saturation and allowed maximum gain up to 27.3 dB. However, the SRS location far from the L-band region reduced the Raman amplification effect and subsequently lowered the transmission gain. From the 1567 nm laser produced by the 1555 nm SRS, another enhancement to the pumping scheme was proposed. The idea was to utilize the 1567 nm laser, which was generated by the ultra-long Raman fiber laser (ULRFL) phenomenon, as a thirdorder pump for a section of passive EDF deployed prior to the end of the transmission span. The transmission gain was improved over the conventional REDFA for 0 dBm signal power but the gain for the lower signal levels was clamped due to the saturation of the passive EDF by the 1567 nm ULRFL. The integration of the conventional R-EDFA architecture with passive EDF section was then performed, with the ULRFL acting as the second-order pump for the passive EDF. A wavelength-selective reflector was incorporated for variation of ULRFL seed wavelength, from which an optimized ULRFL wavelength range was acquired from 1553 to 1557 nm. This amplifier architecture obtained the best gain performance at all signal levels with minimal OSNR penalty. This is attributed to the high ULRFL power and the location of the ULRFL at wavelength with high erbium absorption. The findings demonstrated the performance improvements accorded through the use of the proposed pumping scheme. There is immense potential for further enhancement by optimizing the Raman laser wavelength and striking a balance between efficient pump-to-signal conversion and Raman amplification.